Absorption of dissolved ascorbate by live channel catfish(Ictalurus punctatus) - Thed, Swee T.; Erickson, Marilyn C. (Wiley Periodicals Inc., 1992)
live channel catfish were exposed to 0.3 % sodium ascorbate solution at pH5. Ascorbic acid concentration in the fillets was found to increase from 13ppm. initially (control group) to 51 ppm and 43 ppm for fish exposed to ascorbate for 8 Curd 24 h, respectively. For the group offish exposed to 8 h of ascorbate followedby 16 h of dechlorinated water, pH 7, the fillets contained 27ppm ascorbic acid.Fish which were exposed to water (without ascorbate) at pH 5 for 24 h showeda comparable ascorbic acid level in fillets to those fillets from the control group.The absorption of ascorbate via gills and/or intestines and distribution to required sites within the muscle tissue could serve to increase the stability of the fish filletduring subsequent processing and storage. Introduction of water-soluble antioxidants to aquacultured fish species by this approach requires further exploration.